2013
DOI: 10.1007/s11103-013-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose)polymerases are involved in microhomology mediated back-up non-homologous end joining in Arabidopsis thaliana

Abstract: Besides the KU-dependent classical non-homologous end-joining (C-NHEJ) pathway, an alternative NHEJ pathway first identified in mammalian systems, which is often called the back-up NHEJ (B-NHEJ) pathway, was also found in plants. In mammalian systems PARP was found to be one of the essential components in B-NHEJ. Here we investigated whether PARP1 and PARP2 were also involved in B-NHEJ in Arabidopsis. To this end Arabidopsis parp1, parp2 and parp1parp2 (p1p2) mutants were isolated and functionally characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 67 publications
3
72
0
Order By: Relevance
“…As shown in Figure 7A, two independent brca1 loss-of-function mutants were modestly sensitive to a range of Al concentrations compared with Col-0 wild type, suggesting that BRCA1 plays a role in repair of Al-dependent DNA damage rather than transition of the root tip to endoreduplication. PARP2, in conjunction with PARP1, is a key component of microhomology-mediated end joining, which is one type of nonhomologous end joining (NHEJ) DNA repair mechanism that is related to base excision and single strand break repair (Jia et al, 2013). As shown in Figure 7B, loss of these two key components of microhomology-mediated end joining results in increased sensitivity to Al, consistent with Al acting as a DNA damage agent.…”
Section: Sog1 Binds To the Brca1 Promoter In Vitromentioning
confidence: 70%
See 2 more Smart Citations
“…As shown in Figure 7A, two independent brca1 loss-of-function mutants were modestly sensitive to a range of Al concentrations compared with Col-0 wild type, suggesting that BRCA1 plays a role in repair of Al-dependent DNA damage rather than transition of the root tip to endoreduplication. PARP2, in conjunction with PARP1, is a key component of microhomology-mediated end joining, which is one type of nonhomologous end joining (NHEJ) DNA repair mechanism that is related to base excision and single strand break repair (Jia et al, 2013). As shown in Figure 7B, loss of these two key components of microhomology-mediated end joining results in increased sensitivity to Al, consistent with Al acting as a DNA damage agent.…”
Section: Sog1 Binds To the Brca1 Promoter In Vitromentioning
confidence: 70%
“…As shown in Figure 7B, loss of these two key components of microhomology-mediated end joining results in increased sensitivity to Al, consistent with Al acting as a DNA damage agent. Al hypersensitivity was even more pronounced for a parp1 parp2 ku80 triple loss-of-function mutant, which represents a severe reduction in capability to carry out both classical NHEJ (KU80-related) and alternative NHEJ (PARP1-and PARP2-related) (Jia et al, 2013). These results suggest that Al has substantive negative effects on DNA integrity that in part requires ATR and SOG1-dependent induction of BRCA1 and PARP2 to repair the damage.…”
Section: Sog1 Binds To the Brca1 Promoter In Vitromentioning
confidence: 94%
See 1 more Smart Citation
“…Many proteins involved in the altNHEJ pathway, such as poly (ADP-ribose) polymerase1 (PARP1), meiotic recombination 11 (MRE11)-radiation sensitive 50 (Rad50)-Nijmegen Breakage Syndrome 1 (NBS1), histone H, DNA Ligase III, and XRCC1, have been identified in mammalian cells (Audebert et al, 2004;Rosidi et al, 2008;Cheng et al, 2011). Recent studies have shown that Arabidopsis XRCC1, XPF, Lig1, and PARP1/PARP2 also function in the altNHEJ pathway (Waterworth et al, 2009;Charbonnel et al, 2010Charbonnel et al, , 2011Jia et al, 2013).…”
mentioning
confidence: 99%
“…DSBs are repaired mainly through non-homologous end-joining (NHEJ) and homologous recombination repair (HRR) pathways, which two play complementary roles [7]. PARP1-dependent end-joining (PARP-EJ) is a backup NHEJ repair pathway; when NHEJ is defective, PARP1-EJ pathway is activated [8,9]. PARP inhibitors (such as Olaparib, Iniparib, Veliparib, Rucaparib, and Niraparib), a class of small-molecule drugs inhibiting PARP enzymes, can induce synthetic lethality in HRR deficiency cancer cells [10].…”
Section: Introductionmentioning
confidence: 99%